A remarkable two-dimensional membrane for multifunctional gas separation: halogenated metal-free fused-ring polyphthalocyanine. Issue 28 (13th June 2018) - Meng, Zhaoshun; Zhang, Yadong; Shi, Qi; Liu, Yuzhen; Du, Aijun; Lu, Ruifeng
Abstract : We theoretically demonstrate that fluorinated polyphthalocyanine (F-H2 PPc) is a multifunctional gas separation membrane while chlorinated H2 PPc is only suitable for hydrogen separation from the aspects of permeance and selectivity. Abstract : We theoretically explore the structural and mechanical properties of metal-free fused-ring polyphthalocyanine (H2 PPc) and halogenated H2 PPc (F-H2 PPc and Cl-H2 PPc) membranes, and the energy profiles for gaseous H2, CO, CH4, CO2 and N2 molecules adsorbing on and passing through these monolayers. Importantly, we reconsider in depth the values of the parameters in the definition of permeance, and corroborate the validity of the model from first-principles theory with the results of H2 diffusion from classic molecular dynamics simulations. With well-defined nanosized pores, halogenated H2 PPc monolayers turn out to be multifunctional gas separation membranes, i.e. F-H2 PPc for H2 /CO, H2 /CH4, CO2 /N2, CO2 /CH4, CO/CH4 and N2 /CH4 separation as well as Cl-H2 PPc for H2 /CO, H2 /CH4 and H2 /CO2 separation, which should be of great potential in energy and environmental fields.